Adipokines in Breast Cancer: Decoding Genetic and Proteomic Mechanisms Underlying Migration, Invasion, and Proliferation - Ließem A; Leimer U; Germann GK; Köllensperger E (Breast Cancer: Targets and Therapy)
Anne Ließem, Uwe Leimer, Günter K Germann, Eva Köllensperger Clinic for Plastic, Aesthetic and Reconstructive Surgery, Spine, Orthopedic and Hand Surgery, Preventive Medicine – ETHIANUM, Heidelberg, 69115, GermanyCorrespondence: Eva Köllensperger, Clinic for Plastic, Aesthetic and Reconstructive Surgery, Spine, Orthopedic and Hand Surgery, Preventive Medicine – ETHIANUM, Heidelberg, 69115, Germany, Email Eva.Koellensperger@ethianum.deBackground: Adipokines, bioactive peptides secreted by adipose tissue, appear to contribute to breast cancer development and progression. While numerous studies suggest their role in promoting tumor growth, the exact mechanisms of their involvement are not yet completely understood.Methods: In this project, varying concentrations of recombinant human adipokines (Leptin, Lipocalin-2, PAI-1, and Resistin) were used to study their effects on four selected breast cancer cell lines (EVSA-T, MCF-7, MDA-MB-231, and SK-Br-3). Over a five-day proliferation phase, linear growth was assessed by calculating doubling times and malignancy-associated changes in gene and protein expression were identified using quantitative TaqMan real-time PCR and multiplex protein analysis. Migration and invasion behaviors were quantified using specialized Boyden chamber assays.Results: We found significant, adipokine-mediated genetic and proteomic alterations, with PCR showing an up to 6-fold increase of numerous malignancy-associated genes after adipokine-supplementation. Adipokines further altered protein secretion, such as raising the concentrations of different tumor-associated proteins up to 13-fold. Effects on proliferation varied, however, with most approaches showing significant enhancement in growth kinetics. A concentration-dependent increase in migration and invasion was generally observed, with no significant reductions in any approaches.Conclusion: We could show a robust promoting effect of several adipokines on different breast cancer cells in vitro. Understanding the interaction between adipose tissue and breast cancer cells opens potential avenues for innovative breast cancer prevention and therapy strategies. Our findings indicate that antibodies against specific adipokines could become a beneficial component of clinical breast cancer treatment in the future.Keywords: breast cancer, adipokines, tumor progression, adipose tissue, secretome